Who Goes First? Deaf People and CRISPR Germline Editing - Padden, Carol; Humphries, Jacqueline (Perspectives in biology and medicine, 2020)
The development of CRISPR technology has catapulted the issue of germline editing to the forefront of a debate between the goals of medical advancement and promotion of human diversity. The US National Academy of Sciences and the National Academy of Medicine recommended in a joint report that germline editing should be tightly regulated and pursued only for "serious diseases." A follow-up statement from an international summit on human genome editing emphasized a more general point that "the risks [are] too great to permit clinical trials of germline editing at this time." Here we review their recommendations in the context of genetic deafness, a condition that historically has been viewed by the medical community as a pathology. Deafness does not meet the standard of "serious disease" for experiments with human germline editing, but there is a real concern that scientists may soon begin to do germline editing with deaf individuals because, as we will discuss, they are in many ways ideal subjects for a clinical study of CRISPR, though their condition is neither fatal nor debilitating. In light of this, we worry about the potential for medical overreach and expediency. Drawing from examples of living deaf communities around the world, we propose an expansive view of human diversity that recognizes the value of genetic, linguistic, and cultural diversity to the future health of humankind.